2013
DOI: 10.1590/s2317-17822013005000001
|View full text |Cite
|
Sign up to set email alerts
|

Avaliação audiológica na ataxia espinocerebelar

Abstract: The most evident abnormalities in the audiological evaluation were the predominance of the down-sloping audiometric configuration beginning at 4 kHz bilaterally and the bilateral absence of acoustic reflex at the frequencies of 3 and 4 kHz. In the electrophysiological evaluation, 50% of the patients showed abnormalities with prevalence of an increase of the latency of waves I, II and V and of the interval in the interpeaks I-III, I-V and III-V.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
4
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 15 publications
1
4
0
Order By: Relevance
“…26 In autosomal dominant spinocerebellar ataxia, studies reported 44.1% of abnormalities. 15 In the present study, a greater abnormality was observed in the acoustic immittance measurement, specifically in the acoustic reflex investigation.…”
Section: Discussionsupporting
confidence: 39%
See 2 more Smart Citations
“…26 In autosomal dominant spinocerebellar ataxia, studies reported 44.1% of abnormalities. 15 In the present study, a greater abnormality was observed in the acoustic immittance measurement, specifically in the acoustic reflex investigation.…”
Section: Discussionsupporting
confidence: 39%
“…Knezevic et al and Zeigelboim et al 14 15 evidenced abnormality in 71 and 46.5% of the cases, respectively, in the BAEP assessment of autosomal recessive and dominant spinocerebellar ataxias. These authors found important abnormalities in the brainstem auditory pathways in these types of ataxias.…”
Section: Discussionmentioning
confidence: 89%
See 1 more Smart Citation
“…Some forms of cerebellar ataxia may present with abnormalities in the audiological evaluation, again including the pathology of both peripheral and central auditory pathways. The most evident abnormalities in the audiological evaluation include impedance audiometry, absence of acoustic reflex, and an increase in the latency or absence of waves I, II and V and of the interpeak intervals I-III, I-V, and III-V in electrophysiological evaluation [36,37].…”
Section: Hearing and Cerebellummentioning
confidence: 99%
“…The SCA10 is caused by a repeat expansion of an ATTCT pentanucleotide, in the intron 9 of the gene located in the chromosome 22q13. 3.…”
mentioning
confidence: 99%